High-elastic NFC antenna added with wave-absorbing powder and preparation method thereof
By adding wave absorbing powder and high elastic substances to the NFC antenna to form a high elastic NFC antenna, the problems of poor electromagnetic wave absorption capacity, elasticity and wear resistance of existing NFC antennas are solved, and higher electromagnetic compatibility and mechanical properties are achieved.
Patent Information
- Application Number
- CN202411861941.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-29
AI Technical Summary
The electromagnetic wave absorption capacity, elasticity and wear resistance of existing NFC antennas affect the stability and reliability of NFC technology.
A high elastic NFC antenna with added wave absorbing powder is used. By providing a wave absorbing substrate layer on the ferrite layer, and the NFC antenna layer is pad-printed thereon, bonding with environmentally friendly glue, forming an antenna structure with high electromagnetic compatibility and mechanical properties.
It significantly improves the absorption capacity of NFC antennas to electromagnetic waves, improves electromagnetic compatibility, mechanical properties, elasticity and wear resistance, thereby enhancing the stability and reliability of NFC communication.
Smart Images

Figure BDA0005193406300000031 
Figure BDA0005193406300000051 
Figure BDA0005193406300000161
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of NFC antenna preparation, and in particular relates to a high-elastic NFC antenna with added wave-absorbing powder and a preparation method thereof. Background Art
[0002] NFC technology, as a short-range wireless communication technology, is widely used in mobile payment, access control systems, data transmission and other fields. Its simple and intuitive information exchange method greatly improves the user experience. However, in actual applications, NFC antennas are often interfered by conductive objects such as metal bodies and batteries, resulting in signal attenuation and shortened communication distance, affecting the stability and reliability of NFC technology. Absorbing materials, as a material that can effectively absorb electromagnetic wave energy, can significantly reduce the reflection and scattering of electromagnetic waves on the surfaces of conductive objects such as metals, thereby reducing interference with NFC signals. In NFC antennas, the application of absorbing materials mainly plays two roles: one is to improve communication performance, by reducing electromagnetic interference, improving the stability and reliability of NFC communication; the other is to increase the communication distance. Some absorbing materials can also increase the sensing distance of NFC signals by enhancing the magnetic field strength, making NFC communication more flexible and convenient.
[0003] Patent CN117748156A discloses an absorbing material and a preparation method thereof and a mobile phone NFC antenna. The absorbing material includes absorbing powder and polymer resin. The absorbing powder is a two-dimensional sheet structure and is flatly filled in the polymer resin. The absorbing material of the application mixes the absorbing powder with the polymer resin by flat filling to form a uniform particle distribution, which is easy to be processed into absorbing materials of various shapes. The polymer resin plays the role of filler and binder in the absorbing material, which can make the absorbing powder evenly distributed in the absorbing material, improve the magnetic isolation effect, and can also closely combine the absorbing powder with the polymer water to enhance the mechanical strength and stability of the absorbing material, and achieve a large magnetic permeability and good impedance matching performance. However, the electromagnetic wave absorption capacity, elasticity and wear resistance of the mobile phone NFC antenna prepared by this method still have room for improvement. Summary of the invention
[0004] The purpose of the present invention is to provide a highly elastic NFC antenna with added absorbing powder and a preparation method thereof, so as to solve the technical problems of poor electromagnetic wave absorption capacity, elasticity and wear resistance of the NFC antenna in the prior art.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] The present invention provides a high-elastic NFC antenna with added absorbing powder, wherein the high-elastic NFC antenna comprises a ferrite layer for connecting to an antenna processing signal circuit in a mobile terminal, an absorbing substrate layer arranged on the ferrite layer, and an NFC antenna layer printed on the absorbing substrate layer, wherein the ferrite layer, the absorbing substrate layer and the NFC antenna layer are bonded by an environmentally friendly adhesive, the ferrite layer is composed of soft magnetic ferrite, and the absorbing substrate layer material is composed of absorbing powder and a high-elastic substance.
[0007] Preferably, the method for preparing the microwave absorbing powder comprises the following steps:
[0008] Q1: Add methyl methacrylate, 3-(methacryloyloxy)propyltrimethoxysilane, 2-methyl-2-[(dodecylthiocarbonyl)thio]propionic acid, azobisisobutyronitrile and 1,4-dioxane into a pressure bottle, treat at low temperature, introduce nitrogen and seal, perform oil bath polymerization, cool after the reaction, add dichloromethane to dissolve, perform vacuum rotary evaporation, precipitate, and vacuum dry to obtain product 1;
[0009] Q2: Add isoprene, product 1, di-tert-butyl peroxide and 1,4-dioxane into a pressure bottle, treat at low temperature, introduce nitrogen and seal, perform oil bath polymerization, cool, precipitate, and vacuum dry to obtain product 2;
[0010] Q3: Ball milling the spherical carbonyl iron, then adding product 2 during the milling process, and then vacuum drying to obtain modified carbonyl iron; adding the modified carbonyl iron to deionized water to obtain solution 1, then adding polyacrylic acid to the deionized water, stirring to dissolve, adding triethylamine to obtain solution 2, then slowly adding solution 1 to solution 2, stirring at high speed, freeze drying, heating, grinding and mixing with graphene to obtain absorbing powder.
[0011] In the above process, the synthetic reaction formula of product 2 is as follows:
[0012]
[0013] Preferably, in Q1, the amount ratio of methyl methacrylate, 3-(methacryloyloxy)propyltrimethoxysilane, 2-methyl-2-[(dodecylthiocarbonyl)thio]propionic acid, azobisisobutyronitrile, 1,4-dioxane and dichloromethane is (12-20) g: (2-6) g: (0.22-0.46) g: (0.064-0.082) g: (30-45) mL: (6-10) mL, the low-temperature treatment temperature is -38 to -42°C, the nitrogen introduction time is 30-45 min, the oil bath polymerization reaction temperature is 60-70°C, the time is 4-6 h, cooled to 28-32°C, added to methanol for precipitation, and the vacuum drying temperature is 20-25°C for 6-8 h.
[0014] Preferably, in Q2, the dosage ratio of isopentyl glycol, product 1, di-tert-butyl peroxide and 1,4-dioxane is (30-42.4) g: (0.1-0.2) g: (0.128-0.156) mg: (30-45) mL, the low-temperature treatment temperature is -30 to -50°C, the nitrogen introduction time is 30-45 min, the oil bath polymerization reaction temperature is 110-130°C, the time is 10-14 h, cooled to 25-30°C, added to methanol for precipitation, and the vacuum drying temperature is 30-35°C for 10-14 h.
[0015] Preferably, in Q3, during the ball milling process, the mass ratio of grinding balls to spherical carbonyl iron is (8-10): (1-1.2), anhydrous ethanol is added during the ball milling process, the ball milling time is 10-12h, the amount ratio of spherical carbonyl iron to product 2 is (10-12)g: (1-3)g, the vacuum drying temperature is 60-70°C, and the time is 6-8h; the amount ratio of modified carbonyl iron, polyacrylic acid and triethylamine is (0.18-0.32)g: (0.58-0.87)g: (0.29-0.46)g, the high-speed stirring speed is 10000-12000rpm, the stirring time is 10-15min, the freeze-drying time is 48-60h, and the heating treatment process is: first heated to 220°C, kept warm for 60min, then heated to 300°C, and kept warm for 60min.
[0016] Preferably, the method for preparing the highly elastic material comprises the following steps:
[0017] S1: Add 2-methyl-2-[(dodecylthiothiocarbonyl)thio]propionic acid to a container containing anhydrous ethanol, stir to dissolve, add ethyl methacrylate, stir at room temperature, heat and stir, then inject potassium persulfate aqueous solution, stir to react, add sodium hydroxide aqueous solution, continue stirring to obtain reactant A;
[0018] S2: Add 2-ethylhexyl acrylate to reactant A, stir and emulsify, then add potassium persulfate aqueous solution to react and obtain reactant B; add tert-butyl acrylate to reactant B, deoxygenate and pre-emulsify, then add potassium persulfate aqueous solution to react, after the reaction is completed, add calcium chloride solution, wash, and dry to obtain a highly elastic material.
[0019] In the above process, the synthetic reaction formula of the high elastic material is as follows:
[0020]
[0021] Preferably, in S1, the amount ratio of 2-methyl-2-[(dodecylthiothiocarbonyl)thio]propionic acid, anhydrous ethanol, ethyl methacrylate, potassium persulfate aqueous solution and sodium hydroxide aqueous solution is (0.25-0.5) g: (80-120) mL: (1-2) g: (0.08-0.12) mL: (0.04-0.06) mL, the stirring rate at room temperature is 350-450 rpm, the time is 30-45 min, the temperature of heating and stirring is 70-80°C, the stirring rate is 300-320 rpm, the time is 30-45 min, the mass fraction of potassium persulfate aqueous solution is 10 wt%, the stirring reaction time is 100-120 min, and the mass fraction of sodium hydroxide aqueous solution is 10 wt%.
[0022] Preferably, in S2, the amount ratio of reactant A, 2-ethylhexyl acrylate and potassium persulfate aqueous solution is (1.4-2.7) g: (3.4-5.2) g: (0.01-0.02) mL, the stirring emulsification time is 120-180 min, the mass fraction of potassium persulfate aqueous solution is 10 wt%, and the reaction time is 8-10 h; the amount ratio of reactant B, tert-butyl acrylate, potassium persulfate aqueous solution and calcium chloride solution is (1.2-2.1) g: (1.2-1.6) g: (0.01-0.15) mL: (10-15) mL, the deoxygenation pre-emulsification time is 60-90 min, the reaction time is 4-6 h, the mass fraction of potassium persulfate aqueous solution is 10 wt%, the mass fraction of calcium chloride solution is 1 wt%, and washing is carried out with anhydrous ethanol and deionized water, the drying temperature is 40-50° C., and the time is 20-28 h.
[0023] Preferably, the method for preparing a high-elastic NFC antenna with added absorbing powder comprises the following steps:
[0024] Step 1: Mixing the prepared microwave-absorbing powder with a high-elastic material to obtain a microwave-absorbing substrate layer material;
[0025] Step 2: Use conductive catalytic ink to pad print the NFC antenna traces on the surface of the absorbing substrate layer material, and then adhere the absorbing substrate layer material with the printed NFC antenna traces to the soft ferrite through environmentally friendly glue to obtain a high-elastic NFC antenna with added absorbing powder.
[0026] Preferably, in step 1, the mass ratio of the absorbing powder to the high elastic material is (33-42): (100-120).
[0027] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0028] 1. The present invention first uses methyl methacrylate, 3-(methacryloyloxy)propyltrimethoxysilane, 2-methyl-2-[(dodecylthiocarbonyl)thio]propionic acid, isoprene, spherical carbonyl iron, polyacrylic acid and graphene as raw materials to prepare absorbing powder, and then uses 2-methyl-2-[(dodecylthiocarbonyl)thio]propionic acid, ethyl methacrylate, 2-ethylhexyl acrylate and tert-butyl acrylate as raw materials to prepare a high elastic material. After mixing the two, the high elastic material is used as the absorbing substrate layer material of the NFC antenna, which can effectively improve its absorption capacity of electromagnetic waves, enhance electromagnetic compatibility, mechanical properties, elasticity and wear resistance.
[0029] 2. The present invention uses product 2 to modify the spherical carbonyl iron, and then mixes it with graphene to obtain an absorbing material. The obtained absorbing material is added to the NFC antenna, which can effectively improve its electromagnetic wave absorption performance, improve electromagnetic compatibility and improve its mechanical properties. The modified carbonyl iron can generate magnetic loss under the action of electromagnetic waves, convert electromagnetic wave energy into heat energy, and graphene has excellent conductivity and dielectric properties. It can generate dielectric loss under the action of electromagnetic waves, and convert electromagnetic wave energy through the mechanism of polarization relaxation. The synergistic effect of charge transfer and interface polarization between the two significantly improves the electromagnetic wave absorption performance of NFC materials. At the same time, the addition of absorbing powder can also effectively reduce the electromagnetic wave interference around the NFC material, form an electromagnetic shielding layer, prevent electromagnetic wave leakage and interference, and then improve electromagnetic compatibility. And the modified carbonyl iron is added to the polyacrylic acid as a filler, which can not only fill the gaps and defects, form a compact structure, improve its tensile strength and elasticity, but also improve the overall mechanical properties of the NFC antenna through the interface bonding force.
[0030] 3. The 2-methyl-2-[(dodecylthiothiocarbonyl)thio]propionic acid, ethyl methacrylate, 2-ethylhexyl acrylate and tert-butyl acrylate used in the present invention undergo a polymerization reaction to form a highly elastic material having a long-chain alkyl group and an ester functional group. Adding it to the NFC antenna can effectively improve its elasticity. The addition of potassium persulfate aqueous solution can control the crosslinking density inside the highly elastic material, so that the antenna can better disperse stress when subjected to force, improve its elastic modulus and tensile strength, and the molecular chains present in the highly elastic material have a certain sliding property, which can absorb and disperse external forces, reduce stress concentration and the generation of cracks. At the same time, the hard segments formed by 2-ethylethyl acrylate and tert-butyl acrylate during the polymerization process can improve the hardness of the material surface, and the entanglement points between the molecular chains effectively prevent the external abrasive from eroding the antenna surface, thereby improving its wear resistance. DETAILED DESCRIPTION
[0031] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] Embodiment 1: This embodiment provides a method for preparing a microwave absorbing powder, comprising the following steps:
[0033] Q1: 16 g of methyl methacrylate, 4 g of 3-(methacryloyloxy)propyltrimethoxysilane, 0.34 g of 2-methyl-2-[(dodecylthiothiocarbonyl)thio]propionic acid, 0.073 g of azobisisobutyronitrile and 37.5 mL of 1,4-dioxane were added to a pressure bottle, treated at -40°C, introduced with nitrogen for 30 min and sealed, and polymerized in an oil bath at 60°C for 6 h. After the reaction was completed, the mixture was cooled to 28°C, 8 mL of dichloromethane was added for dissolution, vacuum evaporated, added to methanol for precipitation, and dried under vacuum at 25°C for 8 h to obtain product 1;
[0034] Q2: 36.2 g of isoprene, 0.15 g of product 1, 0.144 mg of di-tert-butyl peroxide and 37.5 mL of 1,4-dioxane were added to a pressure bottle, treated at -40°C, nitrogen was introduced for 30 min and then sealed, polymerized in an oil bath at 120°C for 12 h, cooled to 25°C, added to methanol for precipitation, and vacuum dried at 35°C for 14 h to obtain product 2;
[0035] Q3: 1.1 g of spherical carbonyl iron was ball-milled. During the ball-milling process, the mass of the grinding ball was 9 g. Anhydrous ethanol was added during the ball-milling process. The ball-milling time was 12 h. Subsequently, 0.2 g of product 2 was added during the milling process, and then vacuum-dried at 70 °C for 8 h to obtain modified carbonyl iron. 0.25 g of modified carbonyl iron was added to 5 mL of deionized water to obtain solution 1. Then 0.69 g of polyacrylic acid was added to 10 mL of deionized water. After stirring to dissolve, 0.35 g of triethylamine was added to obtain solution 2. Solution 1 was then slowly added to solution 2. The mixture was stirred at 12,000 rpm for 15 min, freeze-dried for 60 h, and heated to 220 °C for 60 min. The mixture was then heated to 300 °C for 60 min. After grinding, the mixture was mixed with 2 g of graphene to obtain an absorbing powder.
[0036] This embodiment provides a method for preparing a highly elastic material, comprising the following steps:
[0037] S1: 0.37 g of 2-methyl-2-[(dodecylthiothiocarbonyl)thio]propionic acid was added to a container containing 100 mL of anhydrous ethanol, and after stirring to dissolve, 1.5 g of ethyl methacrylate was added, and the mixture was stirred at 450 rpm for 45 min at room temperature, and then the mixture was heated to 80° C. and stirred at 320 rpm for 45 min. Then, 0.1 g of a 10 wt % potassium persulfate aqueous solution was injected, and after stirring for 120 min, 0.05 g of a 10 wt % sodium hydroxide aqueous solution was added, and the mixture was stirred to obtain a reactant A;
[0038] S2: Add 4.3g of 2-ethylhexyl acrylate to 2g of reactant A, stir and emulsify for 180min, then add 0.015mL of 10wt% potassium persulfate aqueous solution, react for 10h to obtain reactant B; add 1.4g of tert-butyl acrylate to 1.6g of reactant B, deoxygenate and pre-emulsify for 90min, then add 0.08mL of 10wt% potassium persulfate aqueous solution to react for 6h, after the reaction, add 12.5mL of 1wt% calcium chloride solution, wash with anhydrous ethanol and deionized water, and dry at 50°C for 24h to obtain a highly elastic material.
[0039] This embodiment provides a method for preparing a high-elastic NFC antenna with added absorbing powder, comprising the following steps:
[0040] Step 1: Mix 36g of the prepared absorbing powder with 110g of a high-elastic material to obtain an absorbing substrate layer material;
[0041] Step 2: Use conductive catalytic ink to pad print the NFC antenna traces on the surface of the absorbing substrate layer material, and then adhere the absorbing substrate layer material with the printed NFC antenna traces to the soft ferrite through environmentally friendly glue to obtain a high-elastic NFC antenna with added absorbing powder.
[0042] Embodiment 2: This embodiment provides a method for preparing a microwave absorbing powder, comprising the following steps:
[0043] Q1: 12 g of methyl methacrylate, 6 g of 3-(methacryloyloxy)propyltrimethoxysilane, 0.22 g of 2-methyl-2-[(dodecylthiothiocarbonyl)thio]propionic acid, 0.082 g of azobisisobutyronitrile and 45 mL of 1,4-dioxane were added to a pressure bottle, treated at -40°C, introduced with nitrogen for 30 min and sealed, and polymerized in an oil bath at 60°C for 6 h. After the reaction was completed, the bottle was cooled to 28°C, 10 mL of dichloromethane was added for dissolution, vacuum evaporated, added to methanol for precipitation, and dried under vacuum at 25°C for 8 h to obtain product 1;
[0044] Q2: 42.4 g of isoprene, 0.1 g of product 1, 0.128 mg of di-tert-butyl peroxide and 30 mL of 1,4-dioxane were added to a pressure bottle, treated at -40°C, nitrogen was introduced for 30 min and then sealed, polymerized in an oil bath at 120°C for 12 h, cooled to 25°C, added to methanol for precipitation, and vacuum dried at 35°C for 14 h to obtain product 2;
[0045] Q3: 1.2g of spherical carbonyl iron was ball-milled. During the ball-milling process, the mass of the grinding ball was 10g. Anhydrous ethanol was added during the ball-milling process. The ball-milling time was 12h. Subsequently, 0.1g of product 2 was added during the milling process, and then vacuum-dried at 70°C for 8h to obtain modified carbonyl iron; 0.18g of modified carbonyl iron was added to 5mL of deionized water to obtain solution 1, and then 0.87g of polyacrylic acid was added to 10mL of deionized water. After stirring and dissolving, 0.46g of triethylamine was added to obtain solution 2, and then solution 1 was slowly added to solution 2. The mixture was stirred at 12000rpm for 15min, freeze-dried for 60h, and heated. First, it was heated to 220°C and kept warm for 60min, then heated to 300°C and kept warm for 60min. After grinding, it was mixed with 2g of graphene to obtain an absorbing powder.
[0046] This embodiment provides a method for preparing a highly elastic material, comprising the following steps:
[0047] S1: 0.25 g of 2-methyl-2-[(dodecylthiothiocarbonyl)thio]propionic acid was added to a container containing 120 mL of anhydrous ethanol, and after stirring to dissolve, 2 g of ethyl methacrylate was added, and the mixture was stirred at 450 rpm for 45 min at room temperature, and then the mixture was heated to 80° C. and stirred at 320 rpm for 45 min. Then, 0.12 g of a 10 wt % aqueous solution of potassium persulfate was injected, and after stirring for 120 min, 0.06 g of a 10 wt % aqueous solution of sodium hydroxide was added, and the mixture was stirred to obtain a reactant A;
[0048] S2: Add 5.2g of 2-ethylhexyl acrylate to 1.4g of reactant A, stir and emulsify for 180min, then add 0.01mL of 10wt% potassium persulfate aqueous solution, react for 10h to obtain reactant B; add 1.6g of tert-butyl acrylate to 1.2g of reactant B, deoxygenate and pre-emulsify for 90min, then add 0.15mL of 10wt% potassium persulfate aqueous solution to react for 6h, after the reaction, add 15mL of 1wt% calcium chloride solution, wash with anhydrous ethanol and deionized water, and dry at 50°C for 24h to obtain a highly elastic material.
[0049] This embodiment provides a method for preparing a high-elastic NFC antenna with added absorbing powder, comprising the following steps:
[0050] Step 1: Mix 33 g of the prepared absorbing powder with 100 g of a high-elastic material to obtain an absorbing substrate layer material;
[0051] Step 2: Use conductive catalytic ink to pad print the NFC antenna traces on the surface of the absorbing substrate layer material, and then adhere the absorbing substrate layer material with the printed NFC antenna traces to the soft ferrite through environmentally friendly glue to obtain a high-elastic NFC antenna with added absorbing powder.
[0052] Embodiment 3: This embodiment provides a method for preparing a microwave absorbing powder, comprising the following steps:
[0053] Q1: 20 g of methyl methacrylate, 2 g of 3-(methacryloyloxy)propyltrimethoxysilane, 0.46 g of 2-methyl-2-[(dodecylthiothiocarbonyl)thio]propionic acid, 0.064 g of azobisisobutyronitrile and 30 mL of 1,4-dioxane were added to a pressure bottle, treated at -40°C, introduced with nitrogen for 30 min and sealed, and polymerized in an oil bath at 60°C for 6 h. After the reaction was completed, the bottle was cooled to 28°C, 6 mL of dichloromethane was added for dissolution, vacuum evaporated, added to methanol for precipitation, and dried in vacuo at 25°C for 8 h to obtain product 1;
[0054] Q2: 30 g of isoprene, 0.2 g of product 1, 0.156 mg of di-tert-butyl peroxide and 45 mL of 1,4-dioxane were added to a pressure bottle, treated at -40°C, nitrogen was introduced for 30 min and then sealed, polymerized in an oil bath at 120°C for 12 h, cooled to 25°C, added to methanol for precipitation, and vacuum dried at 35°C for 14 h to obtain product 2;
[0055] Q3: 1g of spherical carbonyl iron was ball-milled. During the ball-milling process, the mass of the grinding ball was 8g. Anhydrous ethanol was added during the ball-milling process. The ball-milling time was 12h. Subsequently, 0.3g of product 2 was added during the milling process, and then vacuum-dried at 70°C for 8h to obtain modified carbonyl iron; 0.32g of modified carbonyl iron was added to 5mL of deionized water to obtain solution 1, and then 0.58g of polyacrylic acid was added to 10mL of deionized water. After stirring and dissolving, 0.29g of triethylamine was added to obtain solution 2, and then solution 1 was slowly added to solution 2. The mixture was stirred at 12000rpm for 15min, freeze-dried for 60h, and heated. First, it was heated to 220°C and kept warm for 60min, then heated to 300°C and kept warm for 60min. After grinding, it was mixed with 2g of graphene to obtain an absorbing powder.
[0056] This embodiment provides a method for preparing a highly elastic material, comprising the following steps:
[0057] S1: 0.5 g of 2-methyl-2-[(dodecylthiothiocarbonyl)thio]propionic acid was added to a container containing 80 mL of anhydrous ethanol, and after stirring to dissolve, 1 g of ethyl methacrylate was added, and the mixture was stirred at 450 rpm for 45 min at room temperature, and then the mixture was heated to 80° C. and stirred at 320 rpm for 45 min. Then, 0.08 g of a 10 wt % potassium persulfate aqueous solution was injected, and after stirring for 120 min, 0.04 g of a 10 wt % sodium hydroxide aqueous solution was added, and the mixture was stirred to obtain a reactant A;
[0058] S2: Add 3.4 g of 2-ethylhexyl acrylate to 2.7 g of reactant A, stir and emulsify for 180 min, then add 0.02 mL of 10 wt% potassium persulfate aqueous solution, react for 10 h to obtain reactant B; add 1.2 g of tert-butyl acrylate to 2.1 g of reactant B, deoxygenate and pre-emulsify for 90 min, then add 0.01 mL of 10 wt% potassium persulfate aqueous solution and react for 6 h. After the reaction, add 10 mL of 1 wt% calcium chloride solution, wash with anhydrous ethanol and deionized water, and dry at 50°C for 24 h to obtain a highly elastic material.
[0059] This embodiment provides a method for preparing a high-elastic NFC antenna with added absorbing powder, comprising the following steps:
[0060] Step 1: Mix 42g of the prepared absorbing powder with 120g of a high-elastic material to obtain an absorbing substrate layer material;
[0061] Step 2: Use conductive catalytic ink to pad print the NFC antenna traces on the surface of the absorbing substrate layer material, and then adhere the absorbing substrate layer material with the printed NFC antenna traces to the soft ferrite through environmentally friendly glue to obtain a high-elastic NFC antenna with added absorbing powder.
[0062] Embodiment 4: This embodiment provides a method for preparing a microwave absorbing powder, comprising the following steps:
[0063] Q1: 14 g of methyl methacrylate, 3 g of 3-(methacryloyloxy)propyltrimethoxysilane, 0.28 g of 2-methyl-2-[(dodecylthiothiocarbonyl)thio]propionic acid, 0.068 g of azobisisobutyronitrile and 35 mL of 1,4-dioxane were added to a pressure bottle, treated at -40°C, introduced with nitrogen for 30 min and sealed, and polymerized at 60°C in an oil bath for 6 h. After the reaction was completed, the bottle was cooled to 28°C, 7 mL of dichloromethane was added for dissolution, vacuum evaporated, added to methanol for precipitation, and dried under vacuum at 25°C for 8 h to obtain product 1;
[0064] Q2: 33.1 g of isoprene, 0.13 g of product 1, 0.132 mg of di-tert-butyl peroxide and 32 mL of 1,4-dioxane were added to a pressure bottle, treated at -40°C, nitrogen was introduced for 30 min and then sealed, polymerized in an oil bath at 120°C for 12 h, cooled to 25°C, added to methanol for precipitation, and vacuum dried at 35°C for 14 h to obtain product 2;
[0065] Q3: 1.05g of spherical carbonyl iron was ball-milled. During the ball-milling process, the mass of the grinding ball was 8.5g. Anhydrous ethanol was added during the ball-milling process. The ball-milling time was 12h. Subsequently, 0.15g of product 2 was added during the milling process, and then vacuum dried at 70°C for 8h to obtain modified carbonyl iron; 0.21g of modified carbonyl iron was added to 5mL of deionized water to obtain solution 1, and then 0.62g of polyacrylic acid was added to 10mL of deionized water. After stirring and dissolving, 0.32g of triethylamine was added to obtain solution 2, and then solution 1 was slowly added to solution 2, stirred at 12000rpm for 15min, freeze-dried for 60h, and heated. First, it was heated to 220°C and kept warm for 60min, then heated to 300°C and kept warm for 60min. After grinding, it was mixed with 2g of graphene to obtain an absorbing powder.
[0066] This embodiment provides a method for preparing a highly elastic material, comprising the following steps:
[0067] S1: 0.32 g of 2-methyl-2-[(dodecylthiothiocarbonyl)thio]propionic acid was added to a container containing 90 mL of anhydrous ethanol, and after stirring to dissolve, 1.2 g of ethyl methacrylate was added, and the mixture was stirred at 450 rpm for 45 min at room temperature, and then the mixture was heated to 80° C. and stirred at 320 rpm for 45 min. Then, 0.09 g of a 10 wt % aqueous solution of potassium persulfate was injected, and after stirring for 120 min, 0.045 g of a 10 wt % aqueous solution of sodium hydroxide was added, and the mixture was stirred to obtain a reactant A;
[0068] S2: Add 3.8g of 2-ethylhexyl acrylate to 1.6g of reactant A, stir and emulsify for 180min, then add 0.01mL of 10wt% potassium persulfate aqueous solution, react for 10h to obtain reactant B; add 1.3g of tert-butyl acrylate to 1.4g of reactant B, deoxygenate and pre-emulsify for 90min, then add 0.04mL of 10wt% potassium persulfate aqueous solution to react for 6h, after the reaction, add 11mL of 1wt% calcium chloride solution, wash with anhydrous ethanol and deionized water, and dry at 50°C for 24h to obtain a highly elastic material.
[0069] This embodiment provides a method for preparing a high-elastic NFC antenna with added absorbing powder, comprising the following steps:
[0070] Step 1: Mix 35g of the prepared absorbing powder with 105g of a high-elastic material to obtain an absorbing substrate layer material;
[0071] Step 2: Use conductive catalytic ink to pad print the NFC antenna traces on the surface of the absorbing substrate layer material, and then adhere the absorbing substrate layer material with the printed NFC antenna traces to the soft ferrite through environmentally friendly glue to obtain a high-elastic NFC antenna with added absorbing powder.
[0072] Embodiment 5: This embodiment provides a method for preparing a microwave absorbing powder, comprising the following steps:
[0073] Q1: 18 g of methyl methacrylate, 5 g of 3-(methacryloyloxy)propyltrimethoxysilane, 0.42 g of 2-methyl-2-[(dodecylthiothiocarbonyl)thio]propionic acid, 0.08 g of azobisisobutyronitrile and 42 mL of 1,4-dioxane were added to a pressure bottle, treated at -40°C, introduced with nitrogen for 30 min and sealed, and polymerized in an oil bath at 60°C for 6 h. After the reaction was completed, the bottle was cooled to 28°C, 9 mL of dichloromethane was added for dissolution, vacuum evaporated, added to methanol for precipitation, and dried under vacuum at 25°C for 8 h to obtain product 1;
[0074] Q2: 39.3 g of isoprene, 0.17 g of product 1, 0.147 mg of di-tert-butyl peroxide and 42 mL of 1,4-dioxane were added to a pressure bottle, treated at -40°C, nitrogen was introduced for 30 min and then sealed, polymerized in an oil bath at 120°C for 12 h, cooled to 25°C, added to methanol for precipitation, and vacuum dried at 35°C for 14 h to obtain product 2;
[0075] Q3: 1.15g of spherical carbonyl iron was ball-milled. During the ball-milling process, the mass of the grinding ball was 9.5g. Anhydrous ethanol was added during the ball-milling process. The ball-milling time was 12h. Subsequently, 0.25g of product 2 was added during the milling process, and then vacuum dried at 70°C for 8h to obtain modified carbonyl iron; 0.27g of modified carbonyl iron was added to 5mL of deionized water to obtain solution 1, and then 0.79g of polyacrylic acid was added to 10mL of deionized water. After stirring and dissolving, 0.41g of triethylamine was added to obtain solution 2, and then solution 1 was slowly added to solution 2. The mixture was stirred at 12000rpm for 15min, freeze-dried for 60h, and heated. First, it was heated to 220°C and kept warm for 60min, then heated to 300°C and kept warm for 60min. After grinding, it was mixed with 2g of graphene to obtain an absorbing powder.
[0076] This embodiment provides a method for preparing a highly elastic material, comprising the following steps:
[0077] S1: 0.45 g of 2-methyl-2-[(dodecylthiothiocarbonyl)thio]propionic acid was added to a container containing 110 mL of anhydrous ethanol, and after stirring to dissolve, 1.7 g of ethyl methacrylate was added, and the mixture was stirred at 450 rpm for 45 min at room temperature, and then the mixture was heated to 80° C. and stirred at 320 rpm for 45 min. Then, 0.11 g of a 10 wt % potassium persulfate aqueous solution was injected, and after stirring for 120 min, 0.055 g of a 10 wt % sodium hydroxide aqueous solution was added, and the mixture was stirred to obtain a reactant A;
[0078] S2: Add 4.9g of 2-ethylhexyl acrylate to 2.3g of reactant A, stir and emulsify for 180min, then add 0.02mL of 10wt% potassium persulfate aqueous solution, react for 10h to obtain reactant B; add 1.5g of tert-butyl acrylate to 2g of reactant B, deoxygenate and pre-emulsify for 90min, then add 0.12mL of 10wt% potassium persulfate aqueous solution to react for 6h, after the reaction, add 14mL of 1wt% calcium chloride solution, wash with anhydrous ethanol and deionized water, and dry at 50°C for 24h to obtain a highly elastic material.
[0079] This embodiment provides a method for preparing a high-elastic NFC antenna with added absorbing powder, comprising the following steps:
[0080] Step 1: Mix 38g of the prepared absorbing powder with 115g of a high-elastic material to obtain an absorbing substrate layer material;
[0081] Step 2: Use conductive catalytic ink to pad print the NFC antenna traces on the surface of the absorbing substrate layer material, and then adhere the absorbing substrate layer material with the printed NFC antenna traces to the soft ferrite through environmentally friendly glue to obtain a high-elastic NFC antenna with added absorbing powder.
[0082] Comparative Example 1: Compared with Example 1, in the process of preparing the microwave-absorbing powder in Comparative Example 1, no spherical carbonyl iron is added, and other conditions remain unchanged.
[0083] Comparative Example 2: Compared with Example 1, in the process of preparing the high-elastic material in Comparative Example 2, no 2-methyl-2-[(dodecylthiocarbonyl)thio]propionic acid was added, and other conditions remained unchanged.
[0084] Comparative Example 3: Compared with Example 1, in the process of preparing the high-elastic NFC antenna in Comparative Example 3, spherical carbonyl iron is used instead of the absorbing powder, and other conditions remain unchanged.
[0085] Comparative Example 4: Compared with Example 1, in the process of preparing the high-elastic NFC antenna in Comparative Example 4, natural rubber is used instead of the high-elastic material, and other conditions remain unchanged.
[0086] Experimental example: The electromagnetic wave absorption ability of the sample was tested according to GB / T 32596-2016, the tensile strength of the sample was tested according to GB / T33429-2016, and the wear resistance of the sample was tested according to GB / T 1689-2014. The test results are shown in Table 1:
[0087] Table 1
[0088]
[0089]
[0090] The greater the magnetic permeability of the sample, the stronger the absorption capacity of electromagnetic waves. It can be seen from the test results in Table 1 that the high-elastic NFC antennas prepared in Examples 1-5 of the present invention have excellent electromagnetic wave absorption capacity, elasticity and wear resistance. By comparing Comparative Example 1 with Examples 1-5, it can be seen that the addition of spherical carbonyl iron can effectively improve the electromagnetic wave absorption capacity of the high-elastic NFC antenna; by comparing Comparative Example 2 with Examples 1-5, it can be seen that the addition of 2-methyl-2-[(dodecylthiothiocarbonyl)thio] propionic acid can effectively improve the elasticity and wear resistance of the high-elastic NFC antenna; by comparing Comparative Example 3 with Examples 1-5, it can be seen that the use of absorbing powder can effectively improve the electromagnetic wave absorption capacity of the high-elastic NFC antenna; by comparing Comparative Example 4 with Examples 1-5, it can be seen that the use of highly elastic materials can effectively improve the elasticity and wear resistance of the high-elastic NFC antenna.
[0091] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
[0092] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. Highly elastic NFC antenna with added absorbing powder, characterized in that: The highly elastic NFC antenna includes a ferrite layer for connecting to an antenna processing signal circuit in a mobile terminal, an absorbing substrate layer arranged on the ferrite layer, and an NFC antenna layer printed on the absorbing substrate layer. The ferrite layer, the absorbing substrate layer and the NFC antenna layer are bonded together by environmentally friendly glue. The ferrite layer is composed of soft magnetic ferrite, and the absorbing substrate layer material is composed of absorbing powder and highly elastic material.
2. The high-elastic NFC antenna with added absorbing powder according to claim 1, characterized in that: The method for preparing the wave-absorbing powder comprises the following steps: Q1: Add methyl methacrylate, 3-(methacryloyloxy)propyltrimethoxysilane, 2-methyl-2-[(dodecylthiocarbonyl)thio]propionic acid, azobisisobutyronitrile and 1,4-dioxane into a pressure bottle, treat at low temperature, introduce nitrogen and seal, perform oil bath polymerization, cool after the reaction, add dichloromethane to dissolve, perform vacuum rotary evaporation, precipitate, and vacuum dry to obtain product 1; Q2: Add isoprene, product 1, di-tert-butyl peroxide and 1,4-dioxane into a pressure bottle, treat at low temperature, introduce nitrogen and seal, perform oil bath polymerization, cool, precipitate, and vacuum dry to obtain product 2; Q3: Ball milling the spherical carbonyl iron, then adding product 2 during the milling process, and then vacuum drying to obtain modified carbonyl iron; adding the modified carbonyl iron to deionized water to obtain solution 1, then adding polyacrylic acid to the deionized water, stirring to dissolve, adding triethylamine to obtain solution 2, then slowly adding solution 1 to solution 2, stirring at high speed, freeze drying, heating, grinding and mixing with graphene to obtain absorbing powder.
3. The high-elastic NFC antenna with added absorbing powder according to claim 2, characterized in that: In the Q1, the amount ratio of methyl methacrylate, 3-(methacryloyloxy)propyltrimethoxysilane, 2-methyl-2-[(dodecylthiocarbonyl)thio]propionic acid, azobisisobutyronitrile, 1,4-dioxane and dichloromethane is (12-20) g: (2-6) g: (0.22-0.46) g: (0.064-0.082) g: (30-45) mL: (6-10) mL, the low-temperature treatment temperature is -38 to -42°C, the nitrogen introduction time is 30-45 min, the oil bath polymerization reaction temperature is 60-70°C, the time is 4-6 h, the reaction is cooled to 28-32°C, added into methanol for precipitation, and the vacuum drying temperature is 20-25°C for 6-8 h.
4. The high-elastic NFC antenna with added absorbing powder according to claim 2, characterized in that: In Q2, the dosage ratio of isopentyl glycol, product 1, di-tert-butyl peroxide and 1,4-dioxane is (30-42.4) g: (0.1-0.2) g: (0.128-0.156) mg: (30-45) mL, the low-temperature treatment temperature is -30 to -50°C, the nitrogen introduction time is 30-45 min, the oil bath polymerization temperature is 110-130°C, the time is 10-14 h, the reaction is cooled to 25-30°C, added to methanol for precipitation, and the vacuum drying temperature is 30-35°C for 10-14 h.
5. The high-elastic NFC antenna with added absorbing powder according to claim 2, characterized in that: In Q3, during the ball milling process, the mass ratio of grinding balls to spherical carbonyl iron is (8-10): (1-1.2), anhydrous ethanol is added during the ball milling process, the ball milling time is 10-12h, the amount ratio of spherical carbonyl iron to product 2 is (10-12)g: (1-3)g, the vacuum drying temperature is 60-70°C, and the time is 6-8h; the amount ratio of modified carbonyl iron, polyacrylic acid and triethylamine is (0.18-0.32)g: (0.58-0.87)g: (0.29-0.46)g, the high-speed stirring speed is 10000-12000rpm, the stirring time is 10-15min, the freeze-drying time is 48-60h, and the heating treatment process is: first heated to 220°C, kept warm for 60min, then heated to 300°C, and kept warm for 60min.
6. The high-elastic NFC antenna with added absorbing powder according to claim 1, characterized in that: The method for preparing the highly elastic material comprises the following steps: S1: Add 2-methyl-2-[(dodecylthiothiocarbonyl)thio]propionic acid to a container containing anhydrous ethanol, stir to dissolve, add ethyl methacrylate, stir at room temperature, heat and stir, then inject potassium persulfate aqueous solution, stir to react, add sodium hydroxide aqueous solution, continue stirring to obtain reactant A; S2: Add 2-ethylhexyl acrylate to reactant A, stir and emulsify, then add potassium persulfate aqueous solution to react and obtain reactant B; add tert-butyl acrylate to reactant B, deoxygenate and pre-emulsify, then add potassium persulfate aqueous solution to react, after the reaction is completed, add calcium chloride solution, wash, and dry to obtain a highly elastic material.
7. The high-elastic NFC antenna with added absorbing powder according to claim 6, characterized in that: In S1, the amount ratio of 2-methyl-2-[(dodecylthiocarbonyl)thio]propionic acid, anhydrous ethanol, ethyl methacrylate, potassium persulfate aqueous solution and sodium hydroxide aqueous solution is (0.25-0.5) g: (80-120) mL: (1-2) g: (0.08-0.12) mL: (0.04-0.06) mL, the stirring rate at room temperature is 350-450 rpm, the time is 30-45 min, the temperature of heating and stirring is 70-80°C, the stirring rate is 300-320 rpm, the time is 30-45 min, the mass fraction of potassium persulfate aqueous solution is 10 wt%, the stirring reaction time is 100-120 min, and the mass fraction of sodium hydroxide aqueous solution is 10 wt%.
8. The high-elastic NFC antenna with added absorbing powder according to claim 6, characterized in that: In S2, the amount ratio of reactant A, 2-ethylhexyl acrylate and potassium persulfate aqueous solution is (1.4-2.7) g: (3.4-5.2) g: (0.01-0.02) mL, the stirring emulsification time is 120-180 min, the mass fraction of potassium persulfate aqueous solution is 10 wt%, and the reaction time is 8-10 h; the amount ratio of reactant B, tert-butyl acrylate, potassium persulfate aqueous solution and calcium chloride solution is (1.2-2.1) g: (1.2-1.6) g: (0.01-0.15) mL: (10-15) mL, the deoxygenation pre-emulsification time is 60-90 min, the reaction time is 4-6 h, the mass fraction of potassium persulfate aqueous solution is 10 wt%, the mass fraction of calcium chloride solution is 1 wt%, and washing is performed with anhydrous ethanol and deionized water, and the drying temperature is 40-50° C. for 20-28 h.
9. The method for preparing a high-elastic NFC antenna with added absorbing powder according to any one of claims 1 to 8, characterized in that: The following steps are involved: Step 1: Mixing the prepared microwave-absorbing powder with a high-elastic material to obtain a microwave-absorbing substrate layer material; Step 2: Use conductive catalytic ink to pad print the NFC antenna traces on the surface of the absorbing substrate layer material, and then adhere the absorbing substrate layer material with the printed NFC antenna traces to the soft ferrite through environmentally friendly glue to obtain a high-elastic NFC antenna with added absorbing powder.
10. The method for preparing a high-elastic NFC antenna with added absorbing powder according to claim 9, characterized in that: In the step 1, the mass ratio of the absorbing powder to the high elastic material is (33-42): (100-120).